1995
DOI: 10.1016/0014-5793(95)00193-d
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence of involvement of glycosylphosphatidylinositol‐anchored proteins in the heavy metal‐mediated signal delivery into T lymphocytes

Abstract: The biological significance of the action of glycosvlphosphatidylinositol (GPI)-anchored proteins in cell physiology and pathology when stimulated with their natural agonists is not known. Here we provide evidence that GPl-anchored proteins play a crucial role in the recently defined heavy metal (HgCI2)-triggered signal delivery to T lymphocytes. Thiol-reactive HgCI2, a multi-potent crosslinker of cell membrane proteins, induced heavy aggregation of Thy-l, a representative GPI-anchored prot ein, on murine thym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…HgCl 2 is able to directly modify intracellular signaling in T cells [45,46]. We show that HgCl 2 enhances the effect of PMA on CD134 expression, similar to ionomycin.…”
Section: Discussionmentioning
confidence: 70%
“…HgCl 2 is able to directly modify intracellular signaling in T cells [45,46]. We show that HgCl 2 enhances the effect of PMA on CD134 expression, similar to ionomycin.…”
Section: Discussionmentioning
confidence: 70%
“…Correspondingly, we previously suggested that GPI-anchored proteins are obligatorily involved in Hg 2ϩ -induced signaling in T lymphocytes (36,40). To investigate the possible role of the detergentinsoluble membrane raft structure in protein tyrosine phosphorylation and subsequent MAPK family member activation by arsenite, we preincubated thymocytes with ␤ cyclodextrin, which disrupts cholesterol-rich microdomains in the membrane (23,41), before adding NaAsO 2 .…”
Section: The Role Of the Membrane Raft Structure In Arsenite-mediatedmentioning
confidence: 99%
“…Some of these proteins are enzymes, such as placental alkaline phosphatase (5) and erythrocyte acetylcholinesterase (6), whereas others appear to be involved in cell adhesion, complement regulation, or even in transport (1). Still others are thought to play roles in communication between cells (7)(8)(9)(10)(11), and there is accumulating evidence that clustering of some GPI-anchored proteins may represent a new mechanism of signal transduction. Thus macrophages and neutrophils are activated by antibody cross-linking of CD14 (lipopolysaccharide receptor) and CD16 (Fc-␥RIIIB), which leads to cytokine expression and oxidative burst (12)(13)(14), and cross-linking of several T-lymphocyte GPI-anchored proteins produces profound regulatory signals (15)(16)(17)(18).…”
Section: Glycosylphosphatidylinositol (Gpi)mentioning
confidence: 99%